A meta-analysis of the most influential factors of the virtual reality in education for the health and efficiency of students' activity - Oleksandr Yu. Burov; Olha P. Pinchuk (Academy of Cognitive and Natural Sciences, 2023)
Learning focused on assimilation of facts, availability of information, free access to knowledge bases and convenient navigation in local and global networks is not a sufficient condition for the formation of an educated personality, active cognitive activity of the student. In the article, the authors the analysis of virtual reality factors influencing the effectiveness of educational activities and the preservation of the health of students. It is noted that learning in a synthetic environment causes the need to solve new, specific tasks, in particular, the teacher mastering the new role of a facilitator and understanding psychological and psychophysiological problems for health and the effectiveness of learning in a synthetic learning environment, the specificity of cyber-diseases. VR factors have been identified contributing to physiological differences in users: system factors, application and user interaction factors, individual and various factors of perception. Based on the results of research in the field of ergonomics, recommendations have been made, the consideration of which will contribute to reducing the risk of cyber-diseases.